Aplicação de biossorventes no tratamento de efluentes contaminados com corante - Leon, Vitória Brocardo de (2015)
The textile industries use during the production process large amounts of water which after coming into contact with chemicals and dyes build effluents with a strong color, rich in organic matter and mineral salts, which can change the chemical, physical and biological sources. From these facts, this research work aims to use the process of biosorption in the removal of dye Neolan Black WA, since this method uses inexpensive and easily obtainable materials. With the aim of evaluate the effect the solution pH and chemical treatment of biosorbents with a sulphuric acid solution (H2SO4) of 0,5 M concentration on the adsorption process carried out a factorial design 2². Found to graphic surfaces of responses that the best conditions for the removal of the dye with bagasse from sugarcane occurred at pH = 2 and without chemical treatment. The statistical data show that bagasse from sugarcane adsorbed high levels dye, reaching almost 100% removal of the adsorbate, already the orange peel has not proved as efficient at removing dye, although it presented removals nearby to 65%. Were realized analysis of ash content, moisture content, volatile matter content, fixed carbon content, point of zero charge (pHpzc), functional groups of the surface (Boehm's method), scanning electron microscope (SEM) and specific surface area and desorption isotherms of N2 adsorption (BET / BJH ) , in order to characterized the biosorbent material. Lastly were held kinetic studies in order to to valuate the time equilibrium for dye adsorption Neolan Black WA dye by biosorbents bagasse of the sugar and orange peel and adsorption equilibrium studies where it has been found that the Freundlich model was the model that best adjusted with the experimental data for sugar cane and orange (R² = 0,979 for sugarcane and R² = 0,966 for orange ). Through the such evidences we conclude that the adsorption process were studied efficient at removing Neolan Black WA, being that, adsorption processes with sugar showed to be more satisfactory for remove high levels of Neolan Black WA dye compared with orange peel.